A deslegitimação do Parlamento brasileiro na CPI da Petrobrás: um estudo sobre a dinâmica psicopolítica da perda de confiança e credibilidade - Santos, Vanilda Aparecida dos (2016)
The Petrobras corruption scandal revealed by the Lava Jato Operation and daily reported in the national media affected the confidence of investors throughout the world with respect to the Brazilian Market. Nevertheless, the effects of corruption do not affect just the performance of economic institutions, but also generates distrust in public institutions and political agents. Considering the involvement of political authorities in the Petrobras corruption scandal this study has as its objective to analyze how corruption, understood as disobedience to the law, undermines the legitimacy of congressmen ando f Brazilian political institutions. The study is based on the oficial transcriptions of the hearings of the Parlamentary Commission (CPI) investigating the Petrobras scandal and the public hearings that obtained depositions of persons investigated for criminal corruption in Petrobras. Content Analysis according to Laurence Bardin (1977) and a system of interpretation were used as the analytical methodology of the study. Based on the data obtained and analyzed in this study, we conclude that the Parliamentary Commission, in spite of all its judicial powers which are considerably powerful in changing Brazilian policy, did not achieve its goal of investigating the scandal. It was evident the paralysis of the national parliament as the Commission proved to be a microcosm of this institutional crisis. The proceedings were marked by lamentable spectacles from congressmen and where transformed into a game of political interests illustrating the paralysis and institutional crisis. A Parliamentary Investigation Commission increased the distrust of the political class and contributed to the delegitimization of the national congress within Brazilian society